2020
DOI: 10.1073/pnas.1918297117
|View full text |Cite
|
Sign up to set email alerts
|

An energy landscape approach to locomotor transitions in complex 3D terrain

Abstract: Effective locomotion in nature happens by transitioning across multiple modes (e.g., walk, run, climb). Despite this, far more mechanistic understanding of terrestrial locomotion has been on how to generate and stabilize around near–steady-state movement in a single mode. We still know little about how locomotor transitions emerge from physical interaction with complex terrain. Consequently, robots largely rely on geometric maps to avoid obstacles, not traverse them. Recent studies revealed that locomo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(90 citation statements)
references
References 58 publications
6
82
0
Order By: Relevance
“…It was recently suggested that there is an "energy landscape-dominated" regime of locomotion (Othayoth et al, 2020)-when there are large potential energy barriers comparable to or exceeding kinetic energy and/or mechanical work generated by each propulsive cycle or motion, an energy landscape approach is useful for understanding probabilistic locomotor transitions. Our findings supported this notion and expanded the range of this regime of from locomotor transitions in complex 3-D terrain to strenuous self-righting transitions.…”
Section: Expanding Energy Landscape-dominated Regime Of Locomotionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was recently suggested that there is an "energy landscape-dominated" regime of locomotion (Othayoth et al, 2020)-when there are large potential energy barriers comparable to or exceeding kinetic energy and/or mechanical work generated by each propulsive cycle or motion, an energy landscape approach is useful for understanding probabilistic locomotor transitions. Our findings supported this notion and expanded the range of this regime of from locomotor transitions in complex 3-D terrain to strenuous self-righting transitions.…”
Section: Expanding Energy Landscape-dominated Regime Of Locomotionmentioning
confidence: 99%
“…We note that, unlike the simplistic, rigid body model for calculating potential energy barriers in the previous study (Li et al, 2019), our potential energy landscape takes into account how wing opening affects potential energy and thus barriers. Our energy landscape modeling analysis is also different from that in complex 3-D terrain (Othayoth et al, 2020) because here two types of appendages work together to generate locomotor transitions. Because wing opening (primary propulsion) and leg flailing (secondary perturbation) induce different levels of kinetic energy and face different levels of potential energy barriers, their effects must be considered separately to understand the physical mechanism (see discussion of new insight this offers).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bioinspiration & Biomimetics (2020), 10.1088/1748-3190/abac47; https://li.me.jhu.edu/ 25 with large obstacles, animals and robots must often dynamically transition across distinct locomotor modes (Li et al, 2015;Othayoth et al, 2020). Our group's recent work demonstrated that, in different modes, their states are strongly attracted to different basins of an underlying potential energy landscape Han et al, 2017;Othayoth et al, 2020). Our study suggested that body and appendage coordination is crucial for quickly escaping from these attractive landscape basins and having large randomness in coordination is beneficial.…”
Section: Implications For Biological Locomotionmentioning
confidence: 99%
“…We speculate that randomness in coordination could also improve the performance of robots in other strenuous locomotor tasks. When robots are trapped in undesirable metastable states, such as in complex terrain Li et al, 2015;Othayoth et al, 2020), their normal gait (walking, running, etc.) may no longer work.…”
Section: Implications For Roboticsmentioning
confidence: 99%